Answer:
x =
![(c+d)/(a-b)](https://img.qammunity.org/2021/formulas/mathematics/high-school/krwc46ck0rqazyd5fivi7d7c8sxeblebin.png)
Explanation:
Given
ax - c = bx + d ( collect the terms in x together )
Subtract bx from both sides
ax - bx - c = d ( add c to both sides )
ax - bx = c + d ← factor out x from each term on the left side
x(a - b) = c + d ← divide both sides by (a - b )
x =
![(c+d)/(a-b)](https://img.qammunity.org/2021/formulas/mathematics/high-school/krwc46ck0rqazyd5fivi7d7c8sxeblebin.png)